Pain catastrophising, body mass index and depressive symptoms are associated with pain severity in tertiary referral orthopaedic foot/ankle patients - Matthew Holt; Caitlin L. Swalwell; Gayle H. Silveira; Vivienne Tippett; Tom P. Walsh; Simon R. Platt (Journal of Foot and Ankle Research, 2022)
Abstract Introduction Patients with chronic foot/ankle pain are often referred for orthopaedic assessment. Psychological vulnerabilities influence pain states (including foot and ankle), therefore this study aimed to establish the prevalence and relative importance of compromised psychological health to perceived foot/ankle pain severity in people referred to an orthopaedic foot and ankle clinic with non‐urgent presentations. Methods Patients with triaged non‐urgent foot/ankle referrals to the Department of Orthopaedics at Gold Coast University Hospital were recruited over a 12‐month period and completed the Manchester‐Oxford Foot and Ankle Questionnaire which was the primary measure. Participants also completed questionnaires assessing their anthropometric, demographic and health characteristics (Self‐Administered Comorbidity Questionnaire) as well as measures of health‐related quality of life (EuroQol‐5‐Dimensions‐5‐Level Questionnaire and EQ Visual Analogue Scale) and psychological health (Center for Epidemiological Studies‐Depression scale, Pain Catastrophizing Scale and Central Sensitization Inventory). Descriptive statistics were used to summarise participant characteristics and a hierarchical multiple linear regression was employed to establish the extent to which psychological variables explain additional variance in foot/ankle pain severity beyond the effects of participant characteristics (age, sex, body mass index (BMI)). Results One hundred and seventy‐two adults were recruited ((64.0% female), median (IQR) age 60.9 (17.7) years and BMI 27.6 (7.5) kg/m2). Specific psychological comorbidities were prevalent including depressive symptoms (48%), central sensitisation (38%) and pain catastrophising (24%). Age, sex and BMI accounted for 11.7% of the variance in MOXFQ‐index and psychological variables accounted for an additional 28.2%. Pain catastrophising was the most significant independent predictor of foot/ankle pain severity (accounting for 14.4% of variance), followed by BMI (10.7%) and depressive symptoms (2.3%). Conclusions This study demonstrated that specific psychological comorbidities and increased BMI are common in this cohort and that these factors are associated with the symptoms for which patients are seeking orthopaedic assessment. This knowledge should prompt clinicians to routinely consider the psychosocial components of patient presentations and develop non‐operative and pre‐operative treatment strategies which consider these factors with the goal of improving overall patient outcomes.